Feldspar mineralogy - Ribbe, Paul H. (Reviews in mineralogy, 2019)
Volume 2 of Reviews in Mineralogy displays the Short Course on Feldspar Mineralogy in Salt Lake City in October 1975. The workshops on x-ray single-crystal, powder diffraction methods and electron optical techniques as applied to the study of feldspars are the substance of which became the nine chapters of the first edition of Feldspar Mineralogy.It will be noted by readers experienced with feldspars that there are many new ideas appearing in Chapters 3, 4 and 5 that have neither received scrutiny by review (other than ourselves) nor survived practical tests of time in the research community. There is some danger in this, but the editor decided the greater risk was to produce a review volume soon to be outdated. Inevitably, given the different goals of individual authors in their assigned topics, some repetition of material has occurred, although usually with quite different emphases. Chapters 1, 2, 9 and 10, in which plagioclase structures and diffraction patterns and their Al,Si distributions, phase equilibria and exsolution textures are featured, are notable in this regard.